Pengaruh Media Exposure, Ukuran Perusahaan, Profitabilitas Terhadap Corporate Social Responsibility Disclosure Pada Perusahaan Barang Konsumen Primer Sub Sektor Makanan & Minuman Tahun 2013-2022. - Della; Rumia Simanullang (Program Studi Akuntansi Sekolah Tinggi Ilmu Ekonomi Tri Bhakti, 2023)
This study aims to prove empirically the effect of media exposure, firm size, profitability on corporate social responsibility disclosure. This research was conducted in IDX-IC companies listed on the Indonesia Stock Exchange in 2013-2022. Based on the purposive sampling method, the number companies used as the sample of this research were 10 companies with a research period of 10 years. Processing data using SPSS version 25.0 for windows. The results of this research indicate that partially shows that media exposure and profitability has no effect on corporate social responsibility disclosure and firm size has positive effect and significant on corporate social responsibility disclosure about 1,8%.